ANALISIS KREDIT MACET PT DSV PROPERTINDO PADA PROYEK DELIMA CIPTA LAND CABANG PONTIANAK TAHUN 2017 - Narti, Melda; Achmadi, Achmadi; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The study aims to find out the procedure of credit granting by PT DSV Propertindo, what are the causes of bad debts, and how PT DSV Propertindo Delima Cipta Land Project on the branch of Pontianak in handling bad debts. Primary data sources in this study obtained from respondents, by interviews. While the secondary data optained from employees, company documents, and from the library by reviewing and connecting theories that exist. Data has been analyzed by using a purely descriptive method of collecting existing data. Data grouping into categories based on the similarity of data types. With the aim to illustrate the problems studied, than analyzed by using the opinions or theories of experts. The causes of non-perfoming loans in PT DSV Propertindo Project Delima Cipta Land at Pontianak branch is due to the custumer?s unwillingness as much 30%, the location to of the plots is far from the settlement of 20%, the family economy problem 20% and the unidentified froblem of 30%. Efforts made by PT DSV Propertindo Project Delima Cipta Land at Pontianak Branch to handle problem loans by sending notification letters, sending warning latters to the custumer?s address. Credit restructuring is done by extending the loan term.Keywords: NPL, bad debts, non-perfoming loans